Proceedings of GeoShanghai 2018 International Conference: Ground Improvement and Geosynthetics (Springer Singapore, 2018)
This book is the eighth volume of the proceedings of the 4th GeoShanghai International Conference that was held on May 27 - 30, 2018. This book, entitled Ground Improvement and Geosynthetics", presents the latest information on the new technologies and practical applications in various geotechnical engineering projects and advancements on ground improvement and geosynethetics. This volume presents detailed design procedures and examples to demonstrate the applications of the latest ground improvement technologies and innovative geosynethetics in geotechnical engineering. Topics include pile/column technology as foundations, retaining structures, or embankment supports, physical and chemical technologies for soil stabilization and ground improvement, geosynthetic reinforcement for roads, slopes, retaining walls, and foundations.